2020
DOI: 10.1016/j.ijid.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The changing profile of paediatric HIV infection: An experience from the Middle East

Abstract: To describe the clinical and epidemiological profiles of HIV-infected Omani children before and after the implementation of the prevention of mother-to-child transmission of HIV (PMTCT) programme. Methods: A retrospective review of HIV-infected children seen at a national paediatric HIV unit between 1992 and 2015 was performed.Results: Ninety-one HIV-infected children were identified; 59 (65%) were 5 years of age at diagnosis, with 28 (47.5%) of these being <1 year old. The average annual incidence of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The difference in immune status and hormones may also play a role. Although a study from Oman 13 showed slight female (54%) predominance.…”
Section: Discussionmentioning
confidence: 86%
“…The difference in immune status and hormones may also play a role. Although a study from Oman 13 showed slight female (54%) predominance.…”
Section: Discussionmentioning
confidence: 86%